Multilayer electronic component

By introducing SiC and glass of different components into the two-layer sintered electrode structure of Cu sintered electrode, the reliability problems caused by glass erosion and transition temperature are solved, and higher chemical stability and moisture reliability are achieved.

JP2025038874APending Publication Date: 2025-03-19SAMSUNG ELECTRO MECHANICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024138433
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-07
Filing Date
2024-08-20
Publication Date
2025-03-19

AI Technical Summary

Technical Problem

In the prior art, the glass of Cu sintered electrode is eroded by the coating solution, resulting in a decrease in reliability of the germanium capacitor. At the same time, when the transition temperature of the glass decreases, the glass cannot penetrate sufficiently, resulting in a decrease in humidity reliability.

Method used

A two-layer sintered electrode structure is adopted, wherein the first electrode layer comprises Cu, the second electrode layer comprises Cu and SiC, and the area fraction of SiC is adjusted between 5% and 20%, while the glasses of the first electrode layer and the second electrode layer have different components.

Benefits of technology

By adjusting the area fraction of SiC and using glass with different components, the chemical stability and moisture reliability of the germanium capacitor are improved, and the erosion of the plating solution and moisture is prevented.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038874000001_ABST
    Figure 2025038874000001_ABST
Patent Text Reader

Abstract

To solve the problem that the reliability of a multilayer electronic component decreases due to corrosion of glass of a Cu sintered electrode with a plating liquid, and the problem that the moisture resistance reliability of a multilayer electronic component decreases due to failure of sufficient permeation of glass in a main body when the glass transition temperature of glass of the Cu sintered electrode is reduced.SOLUTION: In a sintered electrode structure of two layers including a structure of a first electrode layer and a second electrode containing Cu in an embodiment, the moisture resistance reliability and the fixing strength of a multilayer electronic component can be improved by adjusting the specific gravity of SiC so that the second electrode layer contains SiC or adjusting the glass component included in the first electrode layer and the second electrode layer.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a multilayer electronic component. [Background technology]

[0002] Multilayer ceramic capacitors (MLCCs), a type of multilayer electronic component, are chip-type capacitors that are mounted on printed circuit boards of various electronic products, such as visual devices such as liquid crystal displays (LCDs) and plasma display panels (PDPs), computers, smartphones and mobile phones, and circuits such as on-board chargers (OBCs) and DC-DC converters for electric vehicles, to charge and discharge electricity.

[0003] The glass contained in the basic electrode layer of the existing external electrode mainly contains materials that form a mesh such as Si and Al, and alkali metals or alkaline earth metals can be added to lower the glass transition temperature (Tg). However, when a plating layer is formed on such a basic electrode layer, reliability degradation due to glass erosion may occur, and if the glass transition temperature is lowered too much, the glass may not be able to sufficiently penetrate into the main body, which may cause deterioration in moisture resistance reliability.

[0004] Therefore, there is a need to improve the structure of the external electrodes to prevent deterioration of reliability due to the penetration of moisture from the plating solution or the outside. Summary of the Invention [Problem to be solved by the invention]

[0005] One of the various objects of the present invention is to solve the problem of the glass of the Cu sintered electrode being corroded by the plating solution, resulting in a decrease in the reliability of the multilayer electronic component.

[0006] One of the various objects of the present invention is to solve the problem of deterioration in moisture resistance reliability of multilayer electronic components that occurs when the glass transition temperature of the glass of a Cu sintered electrode is lowered because the glass cannot sufficiently penetrate into the body.

[0007] However, the object of the present invention is not limited to the above-mentioned contents, and can be more easily understood in the course of describing specific embodiments of the present invention. [Means for solving the problem]

[0008] A multilayer electronic component according to one embodiment of the present invention includes a main body including dielectric layers and internal electrodes arranged alternately with the dielectric layers, and an external electrode arranged on the main body, the external electrode including a first electrode layer in contact with the internal electrode and a second electrode layer arranged on the first electrode layer, the first electrode layer including Cu, the second electrode layer including Cu and SiC, and an area fraction of the SiC in the second electrode layer being 5% or more and 20% or less.

[0009] A multilayer electronic component according to one embodiment of the present invention includes a main body including dielectric layers and internal electrodes arranged alternately with the dielectric layers, and an external electrode arranged on the main body, the external electrode including a first electrode layer in contact with the internal electrode and a second electrode layer arranged on the first electrode layer, the first electrode layer including Cu, the second electrode layer including Cu and SiC, and the first electrode layer and the second electrode layer including glasses having different compositions from each other. Effect of the Invention

[0010] One of the various effects of the present invention is that in a two-layer sintered electrode structure having a first electrode layer and a second electrode layer structure containing Cu, the second electrode layer contains SiC and the area fraction of SiC in the second electrode layer is adjusted, thereby improving the chemical resistance and moisture resistance reliability of the multilayer electronic component.

[0011] One of the various effects of the present invention is that in a two-layer sintered electrode structure having a first electrode layer and a second electrode layer structure containing Cu, the second electrode layer contains SiC and the glass compositions contained in the first electrode layer and the second electrode layer are made different, thereby improving the chemical resistance and moisture resistance reliability of the multilayer electronic component.

[0012] However, the various yet significant advantages and effects of the present invention are not limited to the above, and can be more easily understood in the course of describing specific embodiments of the present invention. [Brief description of the drawings]

[0013] [Figure 1] 1 is a perspective view showing a multilayer electronic component according to an embodiment of the present invention; [Diagram 2] 2 is a cross-sectional view taken along line II' in FIG. [Diagram 3] 2 is a cross-sectional view taken along line II-II' in FIG. [Figure 4] FIG. 2 is an exploded perspective view showing a main body according to one embodiment. [Diagram 5] FIG. 3 is an enlarged view of region P in FIG. [Figure 6] FIG. 3 is an enlarged view of a P′ region in FIG. [Figure 7] This is an image taken by a scanning electron microscope (SEM) of a cross section of the second electrode layer when the SiC area fraction exceeds 20%. [Figure 8] This is an image taken with a scanning electron microscope (SEM) of a cross section of a second electrode layer when the SiC area fraction is between 5% and 20%. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, the embodiments of the present invention will be described with reference to specific embodiments and the accompanying drawings. However, the embodiments of the present invention can be modified into several other forms, and the scope of the present invention is not limited to the embodiments described below. Furthermore, the embodiments of the present invention are provided to more completely explain the present invention to those skilled in the art. Therefore, the shapes and sizes of elements in the drawings may be enlarged or reduced (or highlighted or simplified) for clearer explanation, and elements indicated by the same reference numerals in the drawings are the same elements.

[0015] In addition, in the drawings, parts that are not relevant to the description are omitted in order to clearly explain the present invention, and the size and thickness of each component shown in the drawings are arbitrarily shown for convenience of explanation, so the present invention is not necessarily limited by the drawings. Furthermore, components having the same function within the same concept may be described using the same reference numerals. Furthermore, throughout the specification, when a part "includes" a certain component, it does not mean that the part excludes other components, but that the part may further include other components, unless otherwise specified to the contrary.

[0016] In the drawings, a first direction is a direction in which first internal electrodes and second internal electrodes are alternately arranged with a dielectric layer therebetween, or a thickness (T) direction, and among second and third directions perpendicular to the first direction, the second direction can be defined as a length (L) direction and the third direction can be defined as a width (W) direction.

[0017] A multilayer electronic component 100 according to one embodiment of the present invention includes a body including a dielectric layer 111 and internal electrodes 121, 122 arranged alternately with the dielectric layer, and external electrodes 130, 140 arranged on the body, the external electrodes including a first electrode layer 131 in contact with the internal electrode and a second electrode layer 132 arranged on the first electrode layer, the first electrode layer including Cu131a, and the second electrode layer including Cu132a and SiC132c.

[0018] The body 110 includes a dielectric layer 111 and internal electrodes 121 , 122 alternating with the dielectric layer 111 .

[0019] There is no particular limitation on the specific shape of the main body 110. However, as shown in the figure, the main body 110 can be formed in a hexahedron shape or a shape similar thereto. Due to the shrinkage of the ceramic powder contained in the main body 110 during the firing process, the main body 110 can have a substantially hexahedron shape, although it does not have a hexahedron shape with perfect straight lines.

[0020] The main body 110 can have a first surface 1 and a second surface 2 facing each other in a first direction, a third surface 3 and a fourth surface 4 connected to the first surface 1 and the second surface 2 and facing each other in a second direction, and a fifth surface 5 and a sixth surface 6 connected to the first surface 1 and the second surface 2, connected to the third surface 3 and the fourth surface 4, and facing each other in a third direction.

[0021] The plurality of dielectric layers 111 forming the main body 110 are in a fired state, and the boundaries between adjacent dielectric layers 111 can be integrated to such an extent that they are difficult to confirm without using a scanning electron microscope (SEM).

[0022] According to an embodiment of the present invention, the raw material for forming the dielectric layer 111 is not particularly limited as long as sufficient capacitance can be obtained. For example, a barium titanate-based material, a lead composite perovskite-based material, or a strontium titanate-based material can be used. The barium titanate-based material can include BaTiO3-based ceramic powder. Examples of the ceramic powder include BaTiO3, (Ba 1-x Ca x )TiO3 (0 < x < 1) in which Ca (calcium), Zr (zirconium), etc. are partially solid-solved in BaTiO3, Ba(Ti 1-y Ca y )O3 (0 < y < 1), (Ba 1-x Ca x )(Ti 1-y Zr y )O3 (0 < x < 1, 0 < y < 1), or Ba(Ti 1-y Zr y )O3 (0 < y < 1), etc.

[0023] In addition, the raw material for forming the dielectric layer 111 may be a powder such as barium titanate (BaTiO3) to which various ceramic additives, organic solvents, binders, dispersants, etc. may be added according to the purpose of the present invention.

[0024] The average thickness td of the dielectric layer 111 is not particularly limited.

[0025] In order to achieve a smaller size and higher capacity of the multilayer electronic component 100, the average thickness td of the dielectric layer 111 may be 0.35 μm or less, and in order to improve the reliability of the multilayer electronic component 100 under high temperature and high pressure, the average thickness td of the dielectric layer 111 may be 2 μm or more.

[0026] The average thickness td of the dielectric layer 111 may refer to the average thickness td of the dielectric layer 111 disposed between the first internal electrode 121 and the second internal electrode 122.

[0027] The average thickness td of the dielectric layer 111 can be measured by scanning an image of a cross section of the body 110 in the length and thickness direction (LT) using a scanning electron microscope (SEM) with a magnification of 10,000. More specifically, the thickness of one dielectric layer can be measured at 30 equally spaced points in the length direction from the scanned image to obtain an average value. The 30 equally spaced points can be designated as the capacitance forming portion Ac. Furthermore, if such an average value measurement is extended to 10 dielectric layers to measure the average value, the average thickness of the dielectric layer can be further generalized.

[0028] The main body 110 may include a capacitance forming portion Ac disposed inside the main body 110 and including first internal electrodes 121 and second internal electrodes 122 arranged alternately with a dielectric layer 111 in between to form a capacitance, and cover portions 112, 113 formed at the upper and lower portions of the capacitance forming portion Ac in a first direction.

[0029] The capacitance forming portion Ac is a portion that contributes to forming the capacitance of the capacitor, and may be formed by repeatedly stacking a plurality of first internal electrodes 121 and second internal electrodes 122 with the dielectric layer 111 interposed therebetween.

[0030] In an embodiment, an upper cover part 112 may be disposed on one surface of the capacitance forming part Ac in a first direction, and a lower cover part 113 may be included on the other surface of the capacitance forming part Ac in the first direction.

[0031] The upper cover part 112 and the lower cover part 113 may be formed by stacking a single dielectric layer or two or more dielectric layers on the upper and lower surfaces of the capacitance forming part Ac in the thickness direction, respectively, and may basically play a role in preventing damage to the internal electrodes due to physical or chemical stress.

[0032] The upper cover part 112 and the lower cover part 113 do not include an internal electrode and may include the same material as the dielectric layer 111 .

[0033] That is, the upper cover part 112 and the lower cover part 113 may include a ceramic material, for example, a barium titanate (BaTiO3) based ceramic material.

[0034] On the other hand, there is no need to particularly limit the average thickness of the covers 112 and 113. However, in order to more easily achieve miniaturization and high capacity of the multilayer electronic component, the average thickness tc of the covers 112 and 113 can be 15 μm or less.

[0035] The average thickness of the cover parts 112, 113 may mean the size in the first direction, and may be the average value of the size in the first direction of the cover parts 112, 113 measured at five equally spaced points on the upper or lower part of the capacitance forming part Ac.

[0036] In an embodiment, margin portions 114 and 115 may be disposed on one surface and the other surface in the third direction of the capacitance forming portion Ac.

[0037] 2, the margin portions 114, 115 may include a margin portion 114 disposed on the fifth surface 5 of the body 110 and a margin portion 115 disposed on the sixth surface 6. That is, the margin portions 114, 115 may be disposed on both end surfaces in the third direction (width direction) of the body 110.

[0038] The margins 114 and 115 may refer to regions between both ends of the first and second internal electrodes 121 and 122 and the boundary surface of the body 110, as shown in FIG.

[0039] The margins 114 and 115 essentially serve to prevent damage to the internal electrodes due to physical or chemical stress.

[0040] The margin portions 114 and 115 may be formed by applying a conductive paste to the ceramic green sheet except for the areas where the margin portions are to be formed, to form internal electrodes.

[0041] In addition, in order to suppress steps caused by the internal electrodes 121, 122, the laminated internal electrodes can be cut so as to be exposed on the fifth surface 5 and the sixth surface 6 of the main body, and then a single dielectric layer or two or more dielectric layers can be laminated in the third direction (width direction) on both side surfaces of the capacitance forming portion Ac to form margin portions 114, 115.

[0042] On the other hand, there is no need to particularly limit the width of the marginal portions 114, 115. However, in order to more easily achieve a smaller size and higher capacity of the multilayer electronic component, the average width of the marginal portions 114, 115 can be 15 μm or less.

[0043] The average width of the margin portions 114, 115 may mean the average size of the margin portions 114, 115 in the third direction, and may be the average value of the sizes of the margin portions 114, 115 in the third direction measured at five equally spaced points on the side of the capacitance forming portion Ac.

[0044] The internal electrodes 121, 122 and the dielectric layers 111 are alternately arranged in the first direction.

[0045] The internal electrodes 121, 122 may include a first internal electrode 121 and a second internal electrode 122. The first internal electrodes 121 and the second internal electrodes 122 may be alternately arranged to face each other across the dielectric layer 111 constituting the body 110, and may be connected to the third surface 3 and the fourth surface 4 of the body 110, respectively. Specifically, one end of the first internal electrode 121 may be connected to the third surface, and one end of the second internal electrode 122 may be connected to the fourth surface. That is, in one embodiment, the internal electrodes 121, 122 may contact the third surface 3 or the fourth surface 4.

[0046] 1 and 2, the first internal electrode 121 may be spaced apart from the fourth surface 4 and exposed through the third surface 3, and the second internal electrode 122 may be spaced apart from the third surface 3 and exposed through the fourth surface 4. A first external electrode 130 may be disposed on the third surface 3 of the body and connected to the first internal electrode 121, and a second external electrode 140 may be disposed on the fourth surface 4 of the body and connected to the second internal electrode 122.

[0047] That is, the first internal electrode 121 is not connected to the second external electrode 140 but is connected to the first external electrode 130, and the second internal electrode 122 is not connected to the first external electrode 130 but is connected to the second external electrode 140. Therefore, the first internal electrodes 121 may be formed at a certain distance apart on the fourth surface 4, and the second internal electrodes 122 may be formed at a certain distance apart on the third surface 3. At this time, the first internal electrodes 121 and the second internal electrodes 122 may be electrically isolated from each other by the dielectric layer 111 disposed therebetween.

[0048] Referring to FIG. 4, the body 110 may be formed by alternately stacking ceramic green sheets on which the first internal electrodes 121 are printed and ceramic green sheets on which the second internal electrodes 122 are printed, and then firing the stacked ceramic green sheets.

[0049] There are no particular limitations on the material forming the internal electrodes 121 and 122, and any material having excellent electrical conductivity can be used. For example, the internal electrodes 121 and 122 can include one or more of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof.

[0050] The internal electrodes 121 and 122 may be formed by printing a conductive paste for internal electrodes, which includes at least one of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof, on the ceramic green sheet. The method for printing the conductive paste for internal electrodes may be a screen printing method or a gravure printing method, but the present invention is not limited thereto.

[0051] The average thickness te of the internal electrodes 121, 122 is not particularly limited and may vary depending on the purpose. In order to reduce the size of the multilayer electronic component 100, the average thickness te of the internal electrodes 121, 122 may be 0.35 μm or less, and in order to improve the reliability of the multilayer electronic component 100 under high temperature and high pressure, the average thickness te of the internal electrodes 121, 122 may be 2 μm or more.

[0052] The average thickness te of the internal electrodes 121 and 122 may be calculated by measuring the thickness of each of the internal electrode layers extracted from an image obtained by scanning a cross section of the body 110 in the length and thickness direction (LT) with a scanning electron microscope (SEM), and then measuring the average thickness of each of the internal electrodes 121 and 122. The average thickness te of the internal electrodes 121 and 122 may be calculated by measuring the thickness of each of the internal electrode layers extracted from an image obtained by scanning a cross section of the body 110 in the length and thickness direction (LT) with a scanning electron microscope (SEM), and then measuring the average thickness of each of the internal electrode layers extracted from the image obtained by scanning a cross section of the body 110 in the length and thickness direction (LT) with a scanning electron microscope (SEM). The average thickness te of the internal electrodes 121 and 122 may be calculated by measuring the thickness of each of the internal electrode layers extracted from the image obtained by scanning a cross section of the body 110 in the length and thickness direction (LT) with a scanning electron microscope (SEM), and then measuring the average thickness of each of the internal electrode layers extracted from the image obtained by scanning a cross section of the body 110 in the length and thickness direction (LT).

[0053] The outer electrodes 130 , 140 are disposed on the body 110 .

[0054] The external electrodes 130 , 140 may include a first external electrode 130 in contact with the third surface 3 of the body 110 and a second external electrode 140 in contact with the fourth surface 4 .

[0055] Hereinafter, various embodiments of the structure of the external electrodes 130 and 140 will be described with reference to the first external electrode 130. The description of the first external electrode 130 can be similarly applied to the second external electrode 140.

[0056] The external electrode 130 may include a first electrode layer 131 in contact with the internal electrode 121 and a second electrode layer 132 disposed on the first electrode layer 131 .

[0057] The first electrode layer 131 may include Cu 131a and may play a role of ensuring electrical connectivity with the internal electrode 121. At this time, the Cu 131a included in the first electrode layer 131 may form an alloy, an intermetallic compound, or a solid solution with a conductive metal included in the internal electrode 121. For example, when the internal electrodes 121 and 122 include Ni, a Ni-Cu intermetallic compound may be formed at the interface between the internal electrode 121 and the first electrode layer 131, thereby improving the electrical connectivity between the internal electrodes 121 and 122 and the external electrode 130. Meanwhile, the first electrode layer may be formed by applying a conductive paste including Cu and glass to one or more of the third surface 3 and the fourth surface 4 of the body 110 and sintering the paste, but is not limited thereto.

[0058] The second electrode layer 132 may be disposed on the first electrode layer 131. The second electrode layer may include Cu 132a and SiC 132c. The SiC 132c may improve the chemical resistance of the second electrode layer 132 and may delay the sintering of the Cu 132a to control the sintering shrinkage, thereby improving the density. As a result, when the plating layers 133 and 134 are disposed on the second electrode layer 132, the chemical resistance to the plating solution may be improved, and when the conductive resin layer 135 is disposed on the second electrode layer 132, the surface roughness of the second electrode layer 132 may be improved, thereby improving the adhesive strength between the second electrode layer 132 and the conductive resin layer 135.

[0059] The SiC 132c contained in the second electrode layer 132 is a material that is resistant to thermal shock and has excellent chemical stability. When such SiC 132c is contained in the second electrode layer 132, damage to the internal electrodes 121 due to thermal shock and penetration of a plating solution can be prevented, and the strength, chemical resistance, and moisture resistance reliability of the multilayer electronic component 100 can be improved.

[0060] In particular, when the second electrode layer 132 contains Si and Al and further contains an alkali metal or an alkaline earth metal, as in the embodiment, it is possible to prevent a decrease in chemical resistance and moisture resistance reliability that may occur.

[0061] That is, when the second electrode layer 132 contains Si and Al, further contains an alkali metal or an alkaline earth metal, and further contains SiC, the effect of improving the chemical resistance and moisture resistance reliability of the multilayer electronic component 100 can be more significant.

[0062] Meanwhile, since SiC 132c is a material that is resistant to thermal shock as described above, it may not deform even after sintering of the external electrode 130. That is, the shape of the added SiC may be substantially the same as the shape of the SiC present in the second electrode layer 132 of the multilayer electronic component 100. Meanwhile, SiC may be added in the form of a powder having spherical particles in order to control uniform sintering shrinkage of the second electrode layer 132, and at least a portion of the SiC 132c of the second electrode layer 132 according to an embodiment may be spherical.

[0063] On the other hand, if the specific gravity of SiC 132c in the second electrode layer 132 is excessive, the sintering of Cu in the second electrode layer is insufficient due to excessive sintering delay, which may result in a decrease in the moisture resistance reliability of the multilayer electronic component 100. Thus, in one embodiment, the sinterability of the second electrode layer 132 can be appropriately controlled by adjusting the area fraction of SiC 132c in the second electrode layer 132 to 20% or less, thereby preventing a decrease in the moisture resistance reliability of the multilayer electronic component 100. On the other hand, the area fraction of SiC 132c in the second electrode layer 132 is preferably 5% or more in order to impart sufficient roughness to the surface of the second electrode layer 132 to improve the adhesive strength with the conductive resin layer 135 or to improve the moisture resistance reliability.

[0064] Meanwhile, SiC 132c may be substantially only included in the second electrode layer 132, and may not be included in the first electrode layer 131. That is, in one embodiment, the first electrode layer 131 may include SiC at an area fraction of less than 1%.

[0065] Meanwhile, the first electrode layer 131 may include a first glass 131b, and the second electrode layer 132 may include a second glass 132b. In one embodiment, the first glass 131b included in the first electrode layer 131 and the second glass 132b included in the second electrode layer 132 may have different compositions. As a result, the first electrode layer 131 and the second electrode layer 132 may include glasses having different properties, so that more advantageous properties of the external electrode 130 may be ensured.

[0066] Specifically, the first glass 131b may contain Ba and Zn, and the second glass 132b may contain Si and Al. The first electrode layer 131 contains the first glass 131b containing Ba and Zn, which has excellent adhesion to the dielectric layer 111 included in the main body 110, and therefore can prevent the penetration of moisture from the outside of the multilayer electronic component 100. The second electrode layer 132 contains the second glass 132b containing Si and Al, which can suppress sintering shrinkage, and therefore the denseness of the external electrode 130 is improved, thereby improving the chemical resistance of the multilayer electronic component 100 to a plating solution.

[0067] The first glass 131b may further contain Si and Na in addition to Ba and Zn, and the second glass 132b may further contain Sr and Ba in addition to Si and Al. The elements contained in the first glass 131b and the second glass 132b may exist in the form of oxides or as amorphous glass.

[0068] Meanwhile, since the first glass 131b is a glass containing Ba and Zn, it may have a lower glass transition temperature tg than the second glass 132b described below. As a result, a portion of the first glass 131b may diffuse into the dielectric layer 111 of the body 110 during the firing process. That is, in one embodiment, at least a portion of the end E where the dielectric layer 111 contacts the first electrode layer 131 may include the first glass 131b. As a result, the adhesive strength between the external electrode 130 and the body 110 may be improved.

[0069] Meanwhile, the second electrode layer 132 including the second glass 132b may further include at least one of an alkali metal, an alkaline earth metal, and an oxide thereof in order to lower the glass transition temperature Tg. In this case, the glass transition temperature Tg may be lowered by weakening a part of the network structure of Si-Al, but there is a risk of the chemical resistance to the plating solution being reduced. Thus, in one embodiment of the present invention, the second electrode layer 132 includes SiC 132c, so that the glass transition temperature Tg can be lowered and at the same time, the chemical resistance to the plating solution can be prevented from being reduced.

[0070] In one embodiment, the average thickness of the second electrode layer 132 may be greater than the average thickness of the first electrode layer 131. By forming the second electrode layer 132, which has excellent moisture resistance and chemical resistance, to be thicker than the first electrode layer 131, it is possible to improve the moisture resistance reliability and chemical resistance of the multilayer electronic component 100 without reducing the adhesive strength between the external electrode 130 and the main body 110.

[0071] The first electrode layer 131 and the second electrode layer 132 both contain Cu as a conductive metal, and can be distinguished on an image observed through a scanning electron microscope (SEM).

[0072] Specifically, in an image of the external electrode 130 observed through a scanning electron microscope (SEM) after polishing a cross section of the length-width (LW) direction of the multilayer electronic component 100 to 1 / 2 in the thickness (T) direction, the brightness may become darker in the order of Cu 131a, 132a, the first glass 131b, the second glass 132b, and the SiC 132c, and thus the first electrode layer 131 and the second electrode layer 132 can be distinguished. That is, the area including the first glass 131c having the second brightest brightness can be distinguished as the first electrode layer 131, and the area including the second glass 132b having the third brightest brightness and the SiC 132c having the darkest brightness can be distinguished as the second electrode layer 132. Such a difference in brightness can be more clear when the first glass 131b contains Ba and Zn, and the second glass 132b contains Si and Al.

[0073] As an example of a method for measuring the area fraction of SiC in the second electrode layer 132, a cross section of the length-width direction (second direction-third direction) of the laminated electronic component 100 is polished to 1 / 2 in the thickness direction (first direction), and then the region of the second electrode layer 132 is specified by the above-mentioned method for dividing the first electrode layer 131 and the second electrode layer 132, and the area of ​​SIC particles is measured in an image in which Si and C elements are mapped by SEM-EDS (Scanning Electron Microscope-Energy Dispersive Spectroscopy) analysis, and the ratio of the area to the area of ​​the second electrode layer 132 is measured. Such a measurement may be performed under conditions of an acceleration voltage of 15 kV and WD = 15 mm, and the area of ​​the second electrode layer 132 formed on the internal electrodes 121, 122 is divided into three equal parts in the width direction (third direction), and the area fraction of SiC in each region is measured, and the average value is calculated, which may be further generalized.

[0074] The morphology of the SiC in the second electrode layer 132 can also be measured in a manner similar to that for measuring the area fraction of SiC. By measuring the ratio of the long axis to the short axis of the SiC particle, if the ratio is between 0.9 and 1.1, the particle can be determined to be spherical.

[0075] One example of a method for measuring the average thickness of the first electrode layer 131 and the average thickness of the second electrode layer 132 is to polish the cross section of the length-width direction (second direction-third direction) of the laminated electronic component 100 to 1 / 2 in the thickness direction (first direction), specify the region of the second electrode layer 132 by the above-mentioned division method of the first electrode layer 131 and the second electrode layer 132, and then measure the average value of the size in the second direction of the first electrode layer 131 and the average value of the size in the second direction of the second electrode layer 132. Such measurement of the average value of the size in the second direction of the first electrode layer 131 and the second electrode layer 132 can be further generalized by dividing the region of the second electrode layer 132 formed on the internal electrodes 121, 122 into five or more regions in the width direction (third direction) and then taking the average value of the size in the second direction.

[0076] In one embodiment, the external electrode 130 may further include plating layers 133 and 134 disposed on the second electrode layer 132 .

[0077] The plating layers 133 and 134 serve to improve mounting characteristics. The type of plating layer is not particularly limited, and may be a plating layer containing one or more of Ni, Sn, Pd, and alloys thereof, and may be formed of a plurality of layers.

[0078] As a more specific example of the plating layers 133 and 134, the plating layer may be a Ni plating layer or a Sn plating layer, and may be a form in which a Ni plating layer and a Sn plating layer are sequentially formed on the second electrode layer 132, or a form in which a Sn plating layer, a Ni plating layer, and a Sn plating layer are sequentially formed. Also, the plating layer may include a plurality of Ni plating layers and / or a plurality of Sn plating layers.

[0079] 2, in one embodiment, a first plating layer 133 including Ni may be disposed on the second electrode layer 132. This can mitigate thermal shock caused by solder reflow when the multilayer electronic component 100 is mounted on a substrate.

[0080] 2, in one embodiment, a second plating layer 134 including Sn may be disposed on a first plating layer 133 including Ni. The second plating layer 134 includes Sn, and when disposed on the outermost layer of the external electrodes 130, 140, it may serve to improve mounting characteristics.

[0081] In one embodiment, the external electrode 130 may further include a conductive resin layer 135 disposed on the second electrode layer 132, and the conductive resin layer 135 may include a conductive metal and a resin.

[0082] The conductive resin layer 135 can be formed directly on the second electrode layer 132 , and in this case, the plating layers 133 and 134 can be formed on the conductive resin layer 135 .

[0083] The conductive metal may include one or more of Cu, Ni, Ag, Sn, and Cr, and the conductive metal may be present in a dispersed form within the resin of the conductive resin layer 135 .

[0084] The resin may include a resin having high heat resistance, such as, but not limited to, one or more of phenol resin, urea resin, diallyl phthalate resin, melamine resin, guanamine resin, unsaturated polyester resin, polyurethane resin, epoxy resin, acrylic resin, ethyl cellulose resin, aminoalkyd resin, melamine-urea co-condensation resin, silicon resin, and polysiloxane resin.

[0085] The conductive resin layer 135 can play a role in protecting the multilayer electronic component 100 from stress due to warping and stress due to solder reflow that may occur when mounting the multilayer electronic component 100 on a substrate.

[0086] On the other hand, when the second electrode layer 132 contains Cu 132a, second glass 132b, and SiC 132c, roughness is imparted to the surface of the second electrode layer 132, thereby improving the adhesion between the second electrode layer 132 and the conductive resin layer 135.

[0087] On the other hand, even when the conductive resin layer 135 is formed on the second electrode layer 132, it is necessary to appropriately adjust the area fraction of SiC 132c contained in the second electrode layer 132. For example, when the area fraction of SiC 132c in the second electrode layer 132 is less than 5%, the effect of controlling the sintering shrinkage of the second electrode layer 132 is small, and the surface roughness of the second electrode layer 132 may not be sufficiently imparted, and when the ratio of SiC 132c in the second electrode layer 132 exceeds 20%, there is a risk that the second electrode layer 132 will not be sintered. Therefore, in one embodiment, by adjusting the area fraction of SiC 132c in the second electrode layer 132 to 5% or more and 20% or less, it is possible to impart appropriate roughness to the surface of the second electrode layer 132, thereby improving the adhesive force with the conductive resin layer 135, and at the same time ensure appropriate sinterability.

[0088] Below, we will explain an experimental example in which the area fraction of SiC 132c in the second electrode layer 132 was changed to evaluate the density and roughness of the second electrode layer 132, and the adhesion strength and solubility between the second electrode layer 132 and the conductive resin layer 135.

[0089] The powder for forming the dielectric layer was mixed with a dispersant using ethanol and toluene as solvents, and then a binder was mixed to produce a ceramic sheet. Ni electrodes were printed and stacked on the molded ceramic sheet, and the chips that were pressed and cut were pre-fired in an air atmosphere at 400°C, and then fired for about 1 hour at about 1,300°C or less and a hydrogen (H2) concentration of 2.0% or less. A conductive paste containing copper powder and glass frit for forming the first glass was applied and fully fired at a temperature of 600-800°C for 1-2 hours, and then a conductive paste containing copper powder, glass frit for forming the second glass, and SiC spherical particle powder was applied and then a secondary fully fired at a temperature of 600-800°C for 1-2 hours was performed.

[0090] The content of the glass frit for forming the first glass is about 3 to 15 wt %, and the components are Ba, Zn, Si, Na, etc., and the content of the glass frit for forming the second glass is about 3 to 15 wt %, and the components are Si, Al, Sr, Ba, etc. In addition to the above-mentioned components, binders and additives are mixed into each conductive paste.

[0091] Meanwhile, in the experimental example described below, the area fraction of SiC 132c in the second electrode layer 132 was adjusted by adjusting the content of the added SiC, but the present invention is not limited to this.

[0092] The area fraction of SiC 132c measured in the experimental example described later was measured by polishing the cross section of the length-width direction (second direction-third direction) of the laminated electronic component 100 to 1 / 2 in the thickness direction (first direction), specifying the region of the second electrode layer 132 by the above-mentioned division method of the first electrode layer 131 and the second electrode layer 132, measuring the area of ​​SIC particles in an image in which Si and C elements are mapped by SEM-EDS (Scanning Electron Microscope-Energy Dispersive Spectroscopy), and calculating the ratio to the area of ​​the second electrode layer 132. This measurement was performed under conditions of an acceleration voltage of 15 kV and WD = 15 mm, and the area fraction of SiC in each region was measured by dividing the region of the second electrode layer 132 formed on the internal electrodes 121 and 122 into three equal parts in the width direction (third direction), and the average value was calculated.

[0093] (Experimental Example 1) FIG. 7 is an image of a cross section of the second electrode layer 132 when the area fraction of SiC exceeds 20% taken by a scanning electron microscope (SEM).

[0094] Referring to FIG. 7, it can be seen that the specific gravity of SiC 123c in the second electrode layer 132 is excessive, and the degree of sintering of Cu 132a is insufficient, resulting in a decrease in the wettability of the second glass 132b.

[0095] FIG. 8 is an image taken with a scanning electron microscope (SEM) of a cross section of the second electrode layer when the SiC area fraction is equal to or greater than 5% and equal to or less than 20%.

[0096] Referring to FIG. 8, it can be seen that the specific gravity of SiC 123c in the second electrode layer 132 is appropriate and the degree of sintering of Cu 132a is appropriate, so that the second electrode layer 132 can have an appropriate density.

[0097] (Experimental Example 2) Table 1 shows the results of measuring the surface roughness of the second electrode layer 132 according to the SiC area fraction.

[0098] The surface roughness was measured by polishing a cross section of the length-width direction (second direction-third direction) of the laminated electronic component 100 to 1 / 2 in the thickness direction (first direction), and then measuring the roughness on the surface of the second electrode layer 132 (the interface with the conductive resin layer or plating layer). The arithmetic mean roughness Ra, maximum height roughness Rmax, and 10-point mean roughness Rz according to ISO 468 were calculated and compiled in Table 1.

[0099] [Table 1]

[0100] Referring to Table 1, it can be seen that when the SiC area fraction is less than 5%, the effect of improving the surface roughness of the second electrode layer 132 is insufficient. On the other hand, it can be seen that when the SiC area fraction exceeds 20%, the surface roughness increases excessively and becomes irregular. This is expected to be because sintering of the second electrode layer 132 hardly occurs due to an excessive amount of SiC. Therefore, it can be seen that when the area fraction of SiC 123c in the second electrode layer 132 is 5% or more and 20% or less, the surface roughness of the second electrode layer 132 can be improved and appropriate sinterability can be ensured.

[0101] (Experimental Example 3) Table 2 shows the results of evaluating the adhesion strength after forming the conductive resin layer 135 on the second electrode layer 132. The adhesion strength was measured by applying a paste containing copper and epoxy resin to the second electrode layer 132, hardening the conductive resin layer 135, mounting the substrate, and applying a horizontal stress to the substrate with a tensile strength meter to measure the maximum strength when the second electrode layer 132 fell off.

[0102] [Table 2]

[0103] With reference to Table 2, it can be seen that the bonding strength improves as the area fraction of SiC increases. Combining the results of Tables 1 and 2, it can be seen that as the area fraction of SiC 123c increases from second electrode layer 132, the surface roughness of second electrode layer 132 increases, and therefore the bonding strength between second electrode layer 132 and conductive resin layer 135 improves. However, in order to sufficiently improve the surface roughness of second electrode layer 132 and the bonding strength between second electrode layer 132 and conductive resin layer 135, it is preferable that the area fraction of SiC 123c in second electrode layer 132 is 5% or more.

[0104] (Experimental Example 4) [Table 3]

[0105] Solubility (%) is

number

[0106] Referring to Table 3, it can be seen that the solubility decreases as the area fraction of SiC 132c in second electrode layer 132 increases, thereby improving moisture resistance reliability. In particular, it can be seen that the effect of reducing the solubility is significant when the area fraction of SiC 132c in second electrode layer 132 is 5% or more. In other words, it can be seen that the effect of improving the moisture resistance reliability of multilayer electronic component 100 is significant when the area fraction of SiC 123c in second electrode layer 132 is 5% or more.

[0107] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to the above-described embodiments and the attached drawings, but is limited to the scope of the attached claims. Therefore, various substitutions, modifications and changes can be made by a person having ordinary skill in the art within the scope of the technical idea of ​​the present invention described in the claims, and these also belong to the scope of the present invention.

[0108] In addition, the expression "one embodiment" used in the present disclosure does not mean the same embodiment, but is provided to emphasize and describe each different unique feature. However, the above-presented one embodiment does not exclude being realized in combination with the features of another embodiment. For example, even if the matter described in a specific embodiment is not described in another embodiment, it can be understood as a description related to the other embodiment, unless there is a description that is opposite or contradictory to the matter in the other embodiment.

[0109] The terms used in the present disclosure are merely used to describe one embodiment and are not intended to limit the present disclosure. In this case, a singular expression includes a plural expression unless the context clearly indicates otherwise. [Explanation of symbols]

[0110] 100 Multilayer electronic components 110 Main unit 111 Dielectric layer 112, 113 Cover part 114, 115 Margin 121, 122 Internal electrode 130, 140 external electrode 131 1st electrode layer 132 Second electrode layer 133 First plating layer 134 Second plating layer 135 Conductive resin layer

Claims

1. a body including dielectric layers and internal electrodes interleaved with the dielectric layers; an external electrode disposed on the body; the external electrode includes a first electrode layer in contact with the internal electrode and a second electrode layer disposed on the first electrode layer, the first electrode layer includes Cu, and the second electrode layer includes Cu and SiC; an area fraction of the SiC in the second electrode layer is 5% or more and 20% or less.

2. The multilayer electronic component according to claim 1 , wherein the first electrode layer contains the SiC at an area fraction of less than 1%.

3. The multilayer electronic component according to claim 1 , wherein the first electrode layer and the second electrode layer contain glasses having different compositions.

4. 2. The multilayer electronic component according to claim 1, wherein the first electrode layer further includes a first glass containing Ba and Zn, and the second electrode layer further includes a second glass containing Si and Al.

5. The multilayer electronic component according to claim 4 , wherein at least a portion of an end portion of the dielectric layer in contact with the first electrode layer includes a first glass.

6. The multilayer electronic component according to claim 1 , wherein at least a portion of the SiC is spherical.

7. 2. The multilayer electronic component according to claim 1, wherein an average thickness of said second electrode layers is greater than an average thickness of said first electrode layers.

8. The multilayer electronic component according to claim 1 , wherein the external electrodes further include a plating layer disposed on the second electrode layer.

9. The multilayer electronic component according to claim 1 , wherein the external electrodes are disposed on the second electrode layer and further include a conductive resin layer containing a conductive metal and a resin.

10. a body including dielectric layers and internal electrodes interleaved with the dielectric layers; an external electrode disposed on the body; the external electrode includes a first electrode layer in contact with the internal electrode and a second electrode layer disposed on the first electrode layer, the first electrode layer includes Cu, and the second electrode layer includes Cu and SiC; The first electrode layer and the second electrode layer include glasses having different compositions.

11. The multilayer electronic component according to claim 10 , wherein the first electrode layer contains the SiC at an area fraction of less than 1%.

12. The multilayer electronic component according to claim 10 , wherein the first electrode layer further includes a first glass containing Ba and Zn, and the second electrode layer further includes a second glass containing Si and Al.

13. The multilayer electronic component according to claim 12 , wherein at least a portion of an end of the dielectric layer in contact with the first electrode layer includes a first glass.

14. The multilayer electronic component according to claim 10 , wherein at least a portion of the SiC is spherical.

15. The multilayer electronic component according to claim 10 , wherein an average thickness of the second electrode layers is greater than an average thickness of the first electrode layers.

16. The multilayer electronic component according to claim 10 , wherein the external electrodes further include a plating layer disposed on the second electrode layer.

17. 17. The multilayer electronic component according to claim 10, wherein the external electrodes are disposed on the second electrode layer and further include a conductive resin layer containing a conductive metal and a resin.